METEOROLOGICAL DATA AT MIZUHO STATION, ANTARCTICA IN 1984 - YOSHIDA, Minoru; FUJII, Yoshiyuki; KAWADA, Kunio; INAGAWA, Yuzuru; YAMAMOTO, Yuji; TANAKA, Sadahiko (National Institute of Polar Research, 1985)
P(論文) departmental bulletin paper